The Effect of Payment Accounting Information System on the Effectiveness of Internal Control - Ria, Ria (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study aims to test whether the payroll accounting information system affects the company's internal control. This research was conducted in 2022 where the approach used was an approach with quantitative data. The population in this study are companies in the city of Jakarta, with the sample criteria being employees who carry out functions in the accounting or finance and HR departments of the company. The sampling technique used is a saturated sample with a sample of 103 respondents. The collected data is processed using smartPLS software version 4.0. The results of this study indicate that the payroll accounting information system has a positive effect on the effectiveness of the company's internal control. The results of this study support the theory of Theory of Reasoned Action (TRA) which explains that a person or individual will realize that an accounting information system will generate benefits for its users.